The nexus between financial inclusion and financial stability: Credit, savings and asset quality of Kenyan banks - Caroline Kariuki; Gillian Kimundi; Steve Makambi (Kenya Bankers Association (KBA), 2018)
This paper investigates the nexus between bank-based financial inclusion and asset quality of 43 Banks in Kenya using data from 2001 and 2015. Based on a Dynamic Panel (System) GMM employed to investigate the empirical interactions between growth in outstanding bank credit, deposit growth and asset quality, we find that lagged credit growth has a positive significant effect on the NPL Ratio, causing a decrease in asset quality. There is a negative significant contemporaneous relationship between deposit growth and the NPL Ratio; indicating higher stability with higher deposit levels. Increase in the NPL Ratio is also seen to have a negative contemporaneous effect on credit growth, an indication of immediate supply side reactions from banks when a decrease in asset quality is observed. The findings in this paper have important policy implications for both banks and regulators, more so, highlighting the need for policies aimed, not only at management of prudential risks, but at reducing informational asymmetries between banks and borrowers, and promoting alternative platforms providing access to financial services in Kenya.
Keywords: C23; E44; G10; G20; 330; Banks; Asset Quality; Credit Growth; Panel GMM